White Matter Connectivity and Gray Matter Volume Changes Following Donepezil Treatment in Patients With Mild Cognitive Impairment: A Preliminary Study Using Probabilistic Tractography - Kim, Gwang-Won; Park, Shin-Eui; Park, Kwangsung; Jeong, Gwang-Woo (Frontiers in Aging Neuroscience, 2021)
The donepezil treatment is associated with improved cognitive performance in patients with mild cognitive impairment (MCI), and its clinical effectiveness has been well known. However, the impact of the donepezil treatment on the enhanced white matter connectivity in MCI is still unclear. The purpose of this study was to evaluate the thalamo-cortical white matter (WM) connectivity and cortical thickness and gray matter (GM) volume changes in the cortical regions following donepezil treatment in patients with MCI using probabilistic tractography and voxel-based morphometry. Patients with MCI underwent the magnetic resonance examinations before and after 6-month donepezil treatment. Compared with healthy controls, patients with MCI showed the decreased WM connectivity of the thalamo-lateral prefrontal cortex, as well as reduced thickness in the medial/lateral orbitofrontal cortices (p < 0.05). The thalamo-lateral temporal cortex connectivity in patients with MCI was negatively correlated with Alzheimer’s disease assessment scale-cognitive subscale (ADAS-cog) (r = -0.76, p = 0.01). After 6-month donepezil treatment, the average score of Korean version of the mini-mental state examination (K-MMSE) in patients with MCI was improved by 7.9%. However, the patterns of WM connectivity and brain volume change in untreated and treated patients were not significantly different from each other, resulting from multiple comparison correction. These findings will be valuable in understanding of the neurophysiopathological mechanism on MCI as a prodromal phase of Alzheimer’s disease in connection with brain functional connectivity and morphometric change.